2020
DOI: 10.1093/cid/ciaa628
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and In Vitro Resistance of Plasmodium falciparum to Artesunate-Amodiaquine in Cambodia

Abstract: Background Artesunate-amodiaquine is a potential therapy for uncomplicated malaria in Cambodia. Methods Between September 2016 and January 2017, artesunate-amodiaquine efficacy and safety were evaluated in a prospective, open-label, single-arm observational study at health centers in Mondulkiri, Pursat and Siem Reap Provinces, Cambodia. Adults and children with microscopically-confirmed Plasmodium falciparum malaria received … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 30 publications
0
33
0
Order By: Relevance
“…This in turn prevents ART activation, resulting in resistance of early rings to the drug ( Birnbaum et al, 2020 ; Yang et al, 2019 ). Nowadays, ART resistance is frequently accompanied by simultaneous resistance to partner drugs such as mefloquine, piperaquine, or amodiaquine, resulting in high rates of treatment failure and limiting treatment options ( Mairet-Khedim et al, 2020 ; Phyo et al, 2016 ; van der Pluijm et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…This in turn prevents ART activation, resulting in resistance of early rings to the drug ( Birnbaum et al, 2020 ; Yang et al, 2019 ). Nowadays, ART resistance is frequently accompanied by simultaneous resistance to partner drugs such as mefloquine, piperaquine, or amodiaquine, resulting in high rates of treatment failure and limiting treatment options ( Mairet-Khedim et al, 2020 ; Phyo et al, 2016 ; van der Pluijm et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Artemisinin-based combination therapies (ACTs) are the global first-line antimalarial therapies for the treatment of uncomplicated falciparum malaria [ 1 ]. A worrying development is the emergence and spread of Plasmodium falciparum parasites resistant to both artemisinin and partner drugs, compromising ACT efficacy in large areas of Southeast Asia [ 2 5 ]. An even more significant threat is the risk of multidrug resistance spreading further throughout Asia and to the African continent, where most of the malaria burden is clustered [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, resistance to ACTs is occurring as several mutations in pfcrt participate in the resistance to DHA-PIP 3–5 while a mutation in pfmdr1 seems to be associated with AS-AQ treatment failures. 6 Drug-failure to ACTs in the Greater Mekong Subregion (GMS), notably with DHA-PIP, urges the development of new combinations to control and eradicate malaria. AQ-13 is a short chain chloroquine derivative that has been developed to circumvent chloroquine resistance.…”
Section: Introductionmentioning
confidence: 99%
“… 8 However, we have recently shown that the clinical efficacy of AS-AQ precludes its implementation in Cambodia. 6 …”
Section: Introductionmentioning
confidence: 99%